An Algorithmic Approach to Lower Eyelid Malpositions - Seethapathy, G.; Pagadala, Tejaswi; Premalatha, T. (Facial Plastic Surgery, 2025)
Involutional lower eyelid malpositions, such as ectropion and entropion, are frequently encountered in oculoplastic clinics, particularly among elderly patients. These conditions result from age-related weakening of the eyelid structures, leading to eyelid eversion (ectropion) or inversion (entropion). Similarly, lagophthalmos, often caused by facial nerve dysfunction or mechanical factors, presents with incomplete eyelid closure. Aim of this article is to propose a clinical grading and a grade based management algorithm for lower eyelid malpositions.Patients with ectropion may experience tearing, irritation, and conjunctival exposure, while those with entropion often present with foreign body sensation, redness, and corneal damage. Lagophthalmos typically manifests as dryness, exposure keratopathy, and nocturnal eye discomfort.This article proposes a structured, graded algorithm to guide the management of these conditions, offering a systematic, stepwise approach tailored to the severity of eyelid malposition.The algorithms are designed to simplify clinical decision-making by categorizing ectropion, entropion, and lagophthalmos into distinct grades, each with corresponding treatment options. These include both conventional surgical techniques and innovative approaches, allowing for individualized care that addresses both functional and aesthetic concerns.The goal of this graded approach is to optimize patient outcomes, reduce recurrence, and enhance the precision of surgical interventions.By providing a comprehensive framework for managing these complex eyelid disorders, this algorithm serves as an essential tool for ophthalmologists in clinical practice.
Keywords: ectropion; entropion; lagophthalmos; graded algorithm; lower eyelid malposition